Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve this problem, we follow these steps:
### a. Finding the Inverse Function
Given the function \( f(x) = x + 6 \), we need to find the inverse function \( f^{-1}(x) \).
1. Set \( y \) equal to \( f(x) \):
[tex]\[ y = x + 6 \][/tex]
2. Solve for \( x \) in terms of \( y \):
[tex]\[ y = x + 6 \implies y - 6 = x \implies x = y - 6 \][/tex]
3. Rewrite the equation with \( x \) and \( y \) switched (since \( y = f(x) \), therefore \( x = f^{-1}(y) \)):
[tex]\[ f^{-1}(x) = x - 6 \][/tex]
### Correct Choice
The correct choice is A.
So, the inverse function is:
[tex]\[ f^{-1}(x) = x - 6 \text{, for all } x \][/tex]
### b. Verifying the Equation
To verify the inverse function is correct, we need to show that:
1. \( f(f^{-1}(x)) = x \)
2. \( f^{-1}(f(x)) = x \)
#### Verification 1: \( f(f^{-1}(x)) = x \)
Calculate \( f(f^{-1}(x)) \):
1. Substitute \( f^{-1}(x) \) into \( f \):
[tex]\[ f(f^{-1}(x)) = f(x - 6) \][/tex]
2. Evaluate \( f(x - 6) \):
[tex]\[ f(x - 6) = (x - 6) + 6 = x \][/tex]
Thus, \( f(f^{-1}(x)) = x \).
#### Verification 2: \( f^{-1}(f(x)) = x \)
Calculate \( f^{-1}(f(x)) \):
1. Substitute \( f(x) \) into \( f^{-1} \):
[tex]\[ f^{-1}(f(x)) = f^{-1}(x + 6) \][/tex]
2. Evaluate \( f^{-1}(x + 6) \):
[tex]\[ f^{-1}(x + 6) = (x + 6) - 6 = x \][/tex]
Thus, \( f^{-1}(f(x)) = x \).
### Conclusion
The correct inverse function is:
[tex]\[ f^{-1}(x) = x - 6 \text{, for all } x \][/tex]
This equation satisfies the conditions for an inverse function, as verified by [tex]\( f(f^{-1}(x)) = x \)[/tex] and [tex]\( f^{-1}(f(x)) = x \)[/tex].
### a. Finding the Inverse Function
Given the function \( f(x) = x + 6 \), we need to find the inverse function \( f^{-1}(x) \).
1. Set \( y \) equal to \( f(x) \):
[tex]\[ y = x + 6 \][/tex]
2. Solve for \( x \) in terms of \( y \):
[tex]\[ y = x + 6 \implies y - 6 = x \implies x = y - 6 \][/tex]
3. Rewrite the equation with \( x \) and \( y \) switched (since \( y = f(x) \), therefore \( x = f^{-1}(y) \)):
[tex]\[ f^{-1}(x) = x - 6 \][/tex]
### Correct Choice
The correct choice is A.
So, the inverse function is:
[tex]\[ f^{-1}(x) = x - 6 \text{, for all } x \][/tex]
### b. Verifying the Equation
To verify the inverse function is correct, we need to show that:
1. \( f(f^{-1}(x)) = x \)
2. \( f^{-1}(f(x)) = x \)
#### Verification 1: \( f(f^{-1}(x)) = x \)
Calculate \( f(f^{-1}(x)) \):
1. Substitute \( f^{-1}(x) \) into \( f \):
[tex]\[ f(f^{-1}(x)) = f(x - 6) \][/tex]
2. Evaluate \( f(x - 6) \):
[tex]\[ f(x - 6) = (x - 6) + 6 = x \][/tex]
Thus, \( f(f^{-1}(x)) = x \).
#### Verification 2: \( f^{-1}(f(x)) = x \)
Calculate \( f^{-1}(f(x)) \):
1. Substitute \( f(x) \) into \( f^{-1} \):
[tex]\[ f^{-1}(f(x)) = f^{-1}(x + 6) \][/tex]
2. Evaluate \( f^{-1}(x + 6) \):
[tex]\[ f^{-1}(x + 6) = (x + 6) - 6 = x \][/tex]
Thus, \( f^{-1}(f(x)) = x \).
### Conclusion
The correct inverse function is:
[tex]\[ f^{-1}(x) = x - 6 \text{, for all } x \][/tex]
This equation satisfies the conditions for an inverse function, as verified by [tex]\( f(f^{-1}(x)) = x \)[/tex] and [tex]\( f^{-1}(f(x)) = x \)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.